2019
DOI: 10.1149/09203.0003ecst
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Oxide TFT Using Carbon-Doped Ιn2O3 Thin Film Fabricated by Low-Temperature ALD Using Ethylcyclopentadienyl Indium (Ιn-EtCp) and H2O & O3

Abstract: We investigated characteristic of the In2O3 films deposited by various atomic layer deposition (ALD) conditions such as growth temperature and doses of InEtCp precursor and H2O/O3 oxidant gases. A self-limited ALD window was observed in the In2O3 film deposition when an InEtCp and H2O/O3 doses were supplied over 27.6 µmol and 0.09/2.94 mmol, respectively, regardless of the growth temperature. The ratio of In:O:C of the In2O3 films at 150, 170 and 200 ºC were 1:1.16:0.04 (InO1.16C0.04), 1:1.16:0.03 (InO1.16C0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…This sequential process of the reactant pair (WO) resulted in a highly developed GPC. A similar result was observed by Kobayashi et al using In-EtCp as a precursor [117]. The different roles of the two oxidants led to improved results, in that H 2 O releases ligands or byproducts from the surface and O 2 oxidizes the indium.…”
Section: Importance Of Chemical Reaction Related Variables In Binary ...supporting
confidence: 80%
“…This sequential process of the reactant pair (WO) resulted in a highly developed GPC. A similar result was observed by Kobayashi et al using In-EtCp as a precursor [117]. The different roles of the two oxidants led to improved results, in that H 2 O releases ligands or byproducts from the surface and O 2 oxidizes the indium.…”
Section: Importance Of Chemical Reaction Related Variables In Binary ...supporting
confidence: 80%
“…These previous studies reported that InO x generally formed a clear polycrystalline cubic structure with a preferred orientation of (211), (222), or (400), depending on the deposition method and process conditions. Among them, ALD has emerged as a promising deposition technique due to its low-temperature process, good uniformity, excellent step coverage, and controllability of material properties, such as the binding state and crystallinity . In addition, some previous studies have reported that the preferable electrical performance of ALD-processed InO x devices is comparable with those synthesized by a solution and sputtering because of the higher film density induced by a self-limited reaction on the growth surface. ,, For these reasons, the ALD-processed InO x film may be a promising active channel layer for the backplane of next-generation displays. ,, Yeom et al demonstrate the device with the high mobility of 39 cm 2 /V s using the Et 2 InN­(SiMe 3 ) 2 precursor, and Lee et al also present the InO x TFT device using the ([3-(dimethylamino)­propyl]­dimethyl indium) (DADI) precursor. However, high growth or annealing temperatures are required for practical device characteristics, suggesting that it is still challenging to apply to flexible substrates.…”
Section: Introductionmentioning
confidence: 99%
“…17 In addition, some previous studies have reported that the preferable electrical performance of ALD-processed InO x devices is comparable with those synthesized by a solution and sputtering because of the higher film density induced by a self-limited reaction on the growth surface. 3,18,19 For these reasons, the ALD-processed InO x film may be a promising active channel layer for the backplane of next-generation displays. 8,20,21 Yeom et al 8 demonstrate the device with the high mobility of 39 cm 2 /V s using the Et 2 InN(SiMe 3 ) 2 precursor, and Lee et al 21 also present the InO x TFT device using the ([3-(dimethylamino)propyl]dimethyl indium) (DADI) precursor.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24) In 2 O 3 -based metal oxide films have been deposited using various deposition methods such as radio-frequency magnetron sputtering, 25) sol-gel processing, 26) solution processing, 27,28) inkjet printing, 29) chemical vapor deposition (CVD), 30) and atomic layer deposition (ALD). [31][32][33][34][35][36][37][38][39][40][41] In 2 O 3 films deposited via sputtering at room temperature typically have a polycrystalline structure. Moreover, as-grown In 2 O 3 films deposited using solgel, inkjet printing, and CVD methods sometimes contain residual impurities from the precursors; a high-temperature annealing process must then be carried out to reduce these residual impurities.…”
Section: Introductionmentioning
confidence: 99%